2008
DOI: 10.1158/1535-7163.mct-08-0298
|View full text |Cite
|
Sign up to set email alerts
|

Elesclomol induces cancer cell apoptosis through oxidative stress

Abstract: Elesclomol (formerly STA-4783) is a novel small molecule undergoing clinical evaluation in a pivotal phase III melanoma trial (SYMMETRY). In a phase II randomized, double-blinded, controlled, multi-center trial in 81 patients with stage IV metastatic melanoma, treatment with elesclomol plus paclitaxel showed a statistically significant doubling of progression-free survival time compared with treatment with paclitaxel alone. Although elesclomol displays significant therapeutic activity in the clinic, the mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
217
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(232 citation statements)
references
References 35 publications
9
217
0
Order By: Relevance
“…On the basis of the biochemical differences in cancer cells and normal cells, modulation of oxidative stress has recently been re-emerged as a therapeutic strategy to selectively target the destruction of cancer cells. Great efforts have been made for developing selective anticancer therapeutic agents that increase the level of ROS or alternatively suppress the antioxidant systems 1,12,16,33,[39][40][41] . In this regard, we rationally designed a hybrid anticancer drug QCA to exploit oxidation therapy, which can not only increase the level of ROS but also weaken antioxidant systems simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the biochemical differences in cancer cells and normal cells, modulation of oxidative stress has recently been re-emerged as a therapeutic strategy to selectively target the destruction of cancer cells. Great efforts have been made for developing selective anticancer therapeutic agents that increase the level of ROS or alternatively suppress the antioxidant systems 1,12,16,33,[39][40][41] . In this regard, we rationally designed a hybrid anticancer drug QCA to exploit oxidation therapy, which can not only increase the level of ROS but also weaken antioxidant systems simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…S7A) in combination with AC220 and thus was chosen for further study. Elesclomol, which has been evaluated in clinical trials for melanoma, has been shown to selectively transport copper into the mitochondria, to disrupt multiple components of the electron transport chain, and to promote overproduction of mitochondrial ROS (26)(27)(28). In combination with AC220, elesclomol caused synergistic cell killing in both Molm13 cells and MV4-11 cells (Fig.…”
Section: Glutathione Metabolism Is Impaired On Flt3 Inhibition and Fumentioning
confidence: 97%
“…Many developmental redox therapeutics have shown a potentiating effect on pharmacodynamic activity of other anticancer agents and radiation, but offer only modest or no chemotherapeutic benefit if used as single agents (9,29,193). Therefore, many ongoing clinical studies test activity of these agents as combinatorial drugs, consistent with the mechanism of action that involves induction of deviations from redox homeostasis that preferentially sensitize cancer cells to the cytotoxic effects of chemotherapeutic agents (9,29,232,246,288).…”
Section: Redox Chemotherapeuticsmentioning
confidence: 99%